2015
DOI: 10.1089/vbz.2015.1776
|View full text |Cite
|
Sign up to set email alerts
|

Underrecognized Arthropod-Borne and Zoonotic Pathogens in Northern and Northwestern Thailand: Serological Evidence and Opportunities for Awareness

Abstract: Although scrub typhus and murine typhus are well-described tropical rickettsial illnesses, especially in Southeast Asia, only limited evidence is available for rickettsia-like pathogens contributing to the burden of undifferentiated febrile illness. Using commercially available kits, this study measured immunoglobulin G (IgG) antibody seroprevalence for Coxiella burnetii, Ehrlichia chaffeensis, Bartonella henselae, Anaplasma phagocytophilum, and spotted fever group rickettsiae (SFGR) in 375 patients enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…In addition, acute bacterial zoonoses such as rickettsioses, leptospirosis, Q-fever and brucellosis might represent underappreciated causes. This was recently unveiled in studies from south-east Asia and from northern Tanzania, where zoonotic diseases were involved in 26% of admitted adults and children with nonmalarial febrile illnesses [25][26][27]. This study also documented bloodstream infections in 10% of patients, but the actual causes of febrile illnesses remained unknown in one third of adults and two thirds of children, despite careful microbiological evaluation [25].…”
Section: Discussionmentioning
confidence: 70%
“…In addition, acute bacterial zoonoses such as rickettsioses, leptospirosis, Q-fever and brucellosis might represent underappreciated causes. This was recently unveiled in studies from south-east Asia and from northern Tanzania, where zoonotic diseases were involved in 26% of admitted adults and children with nonmalarial febrile illnesses [25][26][27]. This study also documented bloodstream infections in 10% of patients, but the actual causes of febrile illnesses remained unknown in one third of adults and two thirds of children, despite careful microbiological evaluation [25].…”
Section: Discussionmentioning
confidence: 70%
“…Q fever outbreaks in livestock have been reported in Malaysia as recently as 2009 (Bina Rai et al 2011, Norina et al 2011). In humans, Q fever and the seroprevalence of C. burnetii have been reported in rural areas in Malaysia and Thailand (Tay et al 1998, Suputtamongkol et al 2003, Bina Rai et al 2011, Blacksell et al 2015). Unpublished serological studies performed on the Orang Asli in our laboratory have also indicated past C. burnetii exposure in this population.…”
Section: Discussionmentioning
confidence: 99%
“…All Q fever antibody–positive animals were cattle (χ2 14.08, P = 0.003). Interestingly, Xayaboury Province had a clustering of seropositive cattle in seven villages in four districts (Botan, Kenthao, Paklaiy, and Phiang) (Table 3) that share a border with Thailand (Figure 1), where Q fever is endemic 1418. This may be an epidemiologic significant observation with two of the seropositive villages (Nasarn 33.2%; 2/6 positive and Jomphet 50%; 2/4 positive) having two positive animals in the village (Table 3).…”
mentioning
confidence: 99%